THE ROLE OF ECONOMY IN HUMAN DEVELOPMENT (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Human development is an approach focusing on the people themselves and the opportunities they have. With the finding that the economic growth does not bring automatic growth in wealth for everyone, human development focuses on the role of the people themselves in bringing human life to a better condition.